Evaluation of the western blot (WB) kits indetermination index used for the trial of HTLV-1 / 2 infection - Rabelo, G. P. (2006)
Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Laboratório Avançado de Saúde Pública. Salvador, BA, Brasil.